Open University for the School Community - Feitosa, V. L. C.; Santos, V. S.; Santos, L. V.; Lima, C. O.; Santos, I. N.; Machado, J. A.; Aragão, J. A.; Junior, W. L.; Ting, E.; Santos, V. T. G.; Palmeira, J. A. V.; Reis, F. P. (Scientia Plena, 2012)
Learning within the biological sciences requires practical experience. However, traditionally, educational institutions have had limited resources and have lacked teaching laboratories. The Project "Open University for the School Community" aimed to open the doors of the Federal University of Sergipe to the student community from all over the state of Sergipe, in order to show the importance of theoretical and practical knowledge in an interdisciplinary way. From June 2008 to May 2009, community schools were encouraged to visit the university’s laboratories and demonstrations of the microscopic anatomy of different types of cells and tissues, using modern microscopes, were arranged. After the visits, the profiles of the institutions and the real reasons for the visits were investigated using questionnaires. The data were quantified and analyzed. A total of 1700 students from 72 institutions throughout Sergipe were received. Students from private schools (76.39%) predominated, particularly at high school level (62.16%) and from the state capital (66.37%). The main reasons for coming cited by teachers were lack of knowledge and interest in the laboratories. The project expanded the scientific and practical knowledge relating to molecular and cell biology, and constituted an important link between the university and the academic community in this state.